2011
DOI: 10.12693/aphyspola.120.a-158
|View full text |Cite
|
Sign up to set email alerts
|

Google Matrix of the World Trade Network

Abstract: Using the United Nations Commodity Trade Statistics Database we construct the Google matrix of the world trade network and analyze its properties for various trade commodities for all countries and all available years from 1962 to 2009. The trade ows on this network are classied with the help of PageRank and CheiRank algorithms developed for the World Wide Web and other large scale directed networks. For the world trade this ranking treats all countries on equal democratic grounds independent of country richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 27 publications
4
85
0
Order By: Relevance
“…in [14,18,21]), for universities we have significantly stronger concentration around diagonal (K U = K * U ). It looks like that ingoing and outgoing information for articles of universities is approximately conserved like it is approximately the case of commercial flows on the world trade network where the countries try to keep their economic balance [30]. Thus we can say that universities of Oxford, Yale, Uppsala are more communicative (located below diagonal) while those of Cambridge, Princeton, Chicago are much less communicative (located above diagonal).…”
Section: Comparison Of Wrwu and Arwumentioning
confidence: 99%
“…in [14,18,21]), for universities we have significantly stronger concentration around diagonal (K U = K * U ). It looks like that ingoing and outgoing information for articles of universities is approximately conserved like it is approximately the case of commercial flows on the world trade network where the countries try to keep their economic balance [30]. Thus we can say that universities of Oxford, Yale, Uppsala are more communicative (located below diagonal) while those of Cambridge, Princeton, Chicago are much less communicative (located above diagonal).…”
Section: Comparison Of Wrwu and Arwumentioning
confidence: 99%
“…Therefore, to determine the centrality of node i it exploits not only the amount of its incoming links (as approximated for instance by the strength of node i ), but it also considers how its neighbourhood is connected to i. This feature makes the PageRank an appealing indicator and motivates the exploitation of its variants even in several economic and social fields, such as: financial networks and the assessment of systemic risk (Battiston et al, 2012;Hautsch et al, 2014), social networks (Kwak et al, 2010), multiplex networks (Halu et al, 2013), trade networks (Ermann and Shepelyansky, 2011), urban transportation networks (Agryzkov et al, 2012), the ECommerce (Oestreicher-Singer and Sundararajan, 2012), among others.…”
Section: Network Measuresmentioning
confidence: 99%
“…We note that there has been a number of other investigations of the WTN reported in [18,19,20,21,22,23,24]. However, in this work we have the new important elements, developed in [12,13,15]: the analysis of PageRank and CheiRank probabilities corresponding to direct and inverted network flows and related to Import and Export; democratic treatment of countries combined with the contributions of sectors (or products) being proportional to their commercial exchange fractions. We point out that the OECD-WTO TiVA database of economic activities between world countries and activity sectors has been created very recently (2013) and thus this work represents new studies of the WNEA data evolving in time, extending the results reported recently in [15].…”
Section: Introductionmentioning
confidence: 96%